PERSONCREATIVE NATURE OF DESIGN ACTIVITY AS MAN`S SUBJECT CREATIVITY - Захарова, С. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In article the analysis of personcreative nature of design activity is given; essence of creative activity is opened; design achievements which connect harmony, advantage and beauty, utilitarian and aesthetic are analyzed.